Environmental variation drives fine-scale genetic differentiation in the brooding coral Porites panamensis across a marine protected area in the southern Gulf of California - Laura E. Dennis; Fabio Favoretto; Eduardo F. Balart; Adrian Munguia-Vega; Carlos Sánchez-Ortiz; David A. Paz-García (Discover Oceans, 2026)
Genetic differentiation plays a key role in the resilience of reef-building corals under increasing environmental stress. In marine systems, patterns of genetic structure are often shaped by geographic distance and environmental heterogeneity, commonly described as isolation by distance (IBD) and isolation by environment (IBE). Here, we examined patterns of mitochondrial genetic differentiation in the brooding coral Porites panamensis across a marine protected area (MPA) and surrounding reefs in the southern Gulf of California. Using multivariate multiple regression on distance matrices (MMRR), we evaluated the relative effects of along-water geographic distance and environmental differences among sites. At fine spatial scales (≤ 20 km), environmental variation, quantified as Bray–Curtis dissimilarity in benthic community composition, was a significant predictor of genetic differentiation (β_env = 0.100, p = 0.018), whereas geographic distance was not. In contrast, at broader spatial scales (≤ 50 km), genetic differentiation increased with along-water geographic distance (β_geo = 0.0032, p = 0.015), consistent with isolation by distance. These results reveal a scale-dependent pattern of genetic structure, with environmental variation associated with genetic differentiation at finer spatial scales and geographic distance becoming more important at broader scales. Because this study is based on a single mitochondrial marker, the observed patterns reflect mitochondrial lineage differentiation and should be interpreted cautiously with respect to contemporary gene flow. Overall, our findings highlight the importance of spatial scale and environmental heterogeneity in structuring genetic variation within marine protected areas.